Design of three-strand compact spinning system and numerical flow-field simulation for different structures of air-suction guides and suction inserts. Issue 15 (August 2021) - Demir, Murat; Kilic, Musa; Sayin, Serdar; Kiral, Zeki; Balduk, Furkan; Denge, Kıymet Kübra
This study aims to design a compact three-strand spinning approach as inspired by the twist and compact spinning. In the design process, auxiliary parts of twist and pneumatic compact spinning technologies were modified. First, a three-strand funnel and three-groove delivery cylinder were designed to feed three-strand into the drafting zone and control strand space. Then, air-suction guides and suction inserts with different structures of air-inlet slots were designed to create a separate condensing zone for each of the strands. Different structures of the air-suction guide and suction insert were used for modeling the compacting zone and four different systems were introduced. The effectiveness of compacting zones was discussed according to the numerical flow-field simulation studied with SolidWorks Flow Simulation software. Numerical simulation results showed that creating separate condensing zones for three-strand yarns was achieved with all of the new designs. However, the air-guide with longer air-inlet slot channels provided better flow-velocity components and static pressure values. It was also seen that using the same guide with narrowed slots suction insert results in greater flow-velocity components. In the experimental part, the guide with longer air-inlet slots and narrowed slots of suction insert was produced with a 3D printer and used for compact three-strand production. Properties of the compact three-strand yarns were compared with ring three-strand yarns to investigate compacting effects, and it was seen that better yarn properties were obtained with the compact three-strand spinning.